Versions of Hercules in England, c. 1545-1600 - Mayne, E (2016)
This thesis traces some 'versions' of the Graeco-Roman hero and god Hercules in English writing: in early Tudor texts such as Arthur Kelton's panegyrical dynastic poems (1545, 1546), topographical and historical writing such as Holinshed's Chronicles and William Camden’s Britannia (from 1586), and the works of Sir Philip Sidney, Edmund Spenser, and several of Shakespeare’s 1590s plays. It also discusses the representation of Hercules in classical texts key to Hercules' reception in English writing, and, where appropriate, their English translations: Seneca the Younger's Hercules furens, the pseudo-Senecan Hercules Oetaeus; Roman ‘new’ comedy, and classical 'geographical' writing, such as Strabo's Geography, and Pausanias’ Description of Greece. The thesis outlines an early modern Hercules who was a multitude of figures. This is partly because the hero is the product of a historical process of accumulation of mythological materials which, taken together, pose serious moral, generic, and narrative problems. In response, early modern understandings of Hercules often fragment him into several different figures. The thesis shows that this Herculean multiplicity is a resource for early modern writers, and demonstrates the plurality of the Herculeses present in sixteenth century English writing and translations. It also takes an inclusive view of Herculean 'appearances', by acknowledging the variety of ways of 'doing' Hercules across a range of forms: as a rhetorical utterance inherited from the hercle of Roman comedy, as a semi- 'historical' figure operating in the same legendary and geographical spaces as figures from the so-called ‘British History’, and as both a character and a proverbial subject in English dramas and entertainments. Hercules’ early modern plurality also enables the thesis also to engage with the broader questions of what mythological allusion in texts is, and the ways in which it takes place. The thesis identifies classical geographical writing as a significant resource for information about Hercules in the early modern period, as well as mythological stories more generally. It shows how topographical texts both classical and early modern present mythological stories as local phenomena sited in particular geographical spaces, and argues that place forms a significant component of allusion to and creation of mythological narratives in early modern texts. With the help of the terms topos and locus, which suggestively blur geographical, literary, and rhetorical ‘places’, ‘place’ as used in this thesis encompasses both the geographical settings in which many mythological narratives take place, and the way in which these settings are also sites and moments of literary and mythological accumulation in texts.